Hawkeye no. 04, Rio Bravo - Fraction, Matt (Marvel now!, 2015)
"Reeling from recent events, even Hawkeye wants to know what his new status quo is. Who's with him? Who's against him? Who's trying to kill him and why? So many dang questions! And just when Clint's rock bottom couldn't arrive fast enough...his brother shows up. After a lifetime of decisions both good and bad, Clint and Barney Barton have to realize that they are brothers and ultimately, they're the only ones who can save one another. I mean, if they don't kill each other first. Now, the brothers Barton double down against the bad guys as the Clown lays siege to their building. Can Hawkeye keep everyone safe against a killer nobody's even seen yet?"--provided from Amazon.com.